Power, Culture and Situated Research Methodology : Autobiography, Field, Text - Neumann, Cecilie Basberg; Neumann, Iver B. (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2018)
This book explores the extent to which our lives become an important underlying context for data production. Drawing on insights from Gestalt psychology, feminism and post-structuralism, it discusses how to situate yourself in the different phases of research.
1. Introduction -- 2. Pre-field autobiographic situatedness, in-field situatedness, post-field text situatedness -- 3. A century of thinking about situatedness: The Gestalt tradition -- 4. Conceptual inspiration from the Gestalt tradition -- 5. Interview techniques -- 6. Pre-field autobiographic situatedness and post-field textual situatedness -- 7. Philosophy of science: two ways of going about situatedness -- 8. Conclusion: Culture, power, ethics.
Description based on publisher-supplied MARC data.
Keywords: Culture-Study and teaching; International relations; Phenomenology; Political theory; Sociology; Sociology-Research.; International Relations Theory; Cultural Theory; Gender Studies; Phenomenology; Political Theory; Research Methodology